Independence and security of Russia in grain production - V. V. Garkavy; S. A. Raeva (Зерновое хозяйство России)
The purpose of the work is to consider and to assess the level of Russia’s independence in grain production from the standpoint of food security. We used the definition, criteria and indexes of their assessment, recommended by ‘Food Security Doctrine of the Russian Federation’. We intended to give the assessment of the state of food security in the grain production in three directions: in the consumption, in the production and national competitiveness, in the management. But the authors failed to use a number of indexes, as they were intended to evaluate the total food independence and security but not for the assessment of the considered problem according to one separate food resource (e.g. grain). Thus, the system of indexes has been enlarged with extra instruments and there has been collected necessary information to determine their actual values. The authors have concluded that the system of indexes for the assessment of food security, suggested by the Doctrine, needs the improvement and reorientation of its possibilities on the evaluation of the level of independence of country’s supply with food and population with food products of the agricultural, fishery and other sectors of the national economy, participating in the solution of food tasks.